In Memoriam: Ivan Daskalov: 1933 – 2004 - Wald, Alvin (BioMed Central, 2004)
Ivan Daskalov [1933–2004] was a friend who will be missed by many. Neither the quality of a man nor the concept of a friendship can be defined with words. We may only say that both will be missed.